Letter (copy) : Help for the Workers of Spain Fund
028-0123-001 FC/370. Secretary's. 31st December, 1936. PERSONAL. Mr. E. Lynch, The Irish Trade Union Congress, Rooms 34 and 35, 32, Nassau Street, DUBLIN, C.2. Dear Sir, In the absence of Mr. Tewson who is taking a few days' belated "summer" holiday I am acknowledging receipt of your letter of the 21st instant on the above subject. Mr. Tewson will be returning to the office next week when your letter will be placed before him. Yours faithfully, 292/946/28/123